The Pengendalian Kualitas Produk Menggunakan Metode Six Sigma pada UD. Telur Murah - Siti Yulia Salsa Fahrani; Wiji S; Marcellawati (Apik Cahaya Ilmu, 2024)
UD Telur Murah is a business engaged in selling domestic chicken eggs. The problem that occurs is the high number of egg defects. This study aims to determine the causative factors of defects and proposed product quality control using the six sigma method. Egg defect data uses historical data, namely the defect period from September 2022 to August 2023. This research uses SIPOC Diagram, Pareto Diagram, Fishbone Diagram. After identifying the cause of the defect from material factors, namely the level of sress and age in chickens. Method factors are the production process, storage of eggs in crates, and egg packaging. The labor factor is fatigue. Mother nature factors caused by hot air temperatures. Environmental factors are an increase in Ph. Based on the 5W + 1H analysis, the proposal to improve material factors is the provision of vitamins and cage cleanliness that must be maintained, method factors, enforcing SOP, man factors, short rest systems for 10 minutes, air conditioning and adequate ventilation, mother nature factors, periodic checking of room temperature.